An Analysis Of Students’ Difficulties In Translating Poetry From English To Indonesian at HKBP Nommensen University - Sinambela, Erika; Pakpahan, Carolina; Manurung, Lastri Wahyuni; Dakhi, Adoramos (Jurnal Ilmu Sosial Mamangan, 2025)
This research investigates the challenges faced by students in translating poetry from English to Indonesian at HKBP Nommensen University. The complexity of poetic language, characterized by symbolic meanings, figures of speech, and ungrammatical structures, significantly complicates the translation process. A descriptive qualitative methodology was employed, utilizing a poetry translation test and interviews with 20 students. The findings reveal that students predominantly struggle with lexical choices, contextual understanding, and grammatical accuracy, resulting in ineffective translations. Most participants indicated difficulties in selecting appropriate diction and understanding poetic nuances, often leading to inaccuracies. The study concludes that enhancing vocabulary and translation skills through targeted instructional strategies could improve student performance in translating poetry. Recommendations for educators and students are provided to address these challenges effectively.